The landing strip - Kader Attia - Attia, Kader 1970- (Hayward Gallery Publishing, 2019)
French Algerian artist Kader Attia has often focused his work on marginalised communities or people living on the periphery of society ? whether LGBTQ, illegal immigrants, or the mentally or physically disabled.00His photographic series, 'La Piste d'atterrissage' (Landing Strip) (2000-2002) offers psychologically complex and astonishingly intimate portraits of a community of transgender Algerian prostitutes in Paris, many of whom were illegal immigrants. The artist developed close relationships with members of this community whilst assisting them in their efforts to gain legal residence in France, and his photographs portray the full spectrum of their existence, from precarious work lives to everyday domestic life and moments of personal happiness
Published on the occasion of the exhibition "Kader Attia: The Museum of Emotion", Hayward Gallery, London, 13 February - 6 May 2019
Keywords: Attia, Kader -- 1970-; Geschichte 2000-2002; LGBT -- Motiv; Fotografie; Ausstellungskatalog -- Hayward Gallery -- 13.02.2019-06.05.2019 -- London; Bildband